A Global Multi-Sensor Dataset of Surface Water Indices from Landsat-8 and Sentinel-2 Satellite Measurements - Yohei Miura; Mohammad Shamsudduha; Anawat Suppasri; Daisuke Sano (Scientific Data)
Abstract Spatiotemporal mapping of surface water extent constitutes a valuable dataset for the management of water resources, the monitoring of flood- and drought-affected areas, and the conservation of wetlands and freshwater ecosystems. Surface water indices, derived from optical satellite data, serve as effective indicators for estimating surface water coverage. However, global-scale datasets featuring high-resolution surface water mapping using multiple water indices remain scarce and constrained in temporal and spatial scope. Here, we present monthly surface-water maps derived from three water indices, Normalized Difference Water Index (NDWI), Modified NDWI (MNDWI), and Water Index 2015 (WI2015), utilizing high-resolution earth observation satellite data from Landsat-8 and Sentinel-2 for the period January 2019 to December 2021. These maps will be regularly updated as new satellite data become available. These water index mappings provide a baseline for projecting the distribution of surface-water resources and deliver critical information for the sustainable management of surface water resources under the challenges posed by the global climate change.